Peningkatan keterampilan menyimpulkan melalui model pjbl (project based learning) pada pembelajaran IPA - Shelta Yunianingrum; Idam Ragil Widianto Atmojo; Hadiyah Hadiyah (Didaktika Dwija Indria, 2019)
The purpose of this study is describing the improvement concluding skills through the PjBL model (Project Based Learning) thru Science learning on 3rd grade in elementary school the academic year 2017/2018. The method of this research is Classroom Action Research is done in two cycles. Each cycle consists of four steps i.e. planning, action, observation, and reflection. The subject is 3rd grade at one of elemetary school which consist of 21 students. The Data collection techniques are using observation, interviews, tests, and dokumnetasi. The validity of the data using triangulation technique and content validity. Technique of data analysis is using the interactive model analysis. The results showed an increase at each meeting of classical achievement, from 0% in pre cycle, increase to 47,61% in cycle I and end up in 85,17% on cycle II. There are 19.04% (4 students) who scored < 80, it mean that they don’t pass the minimum criteria.. The reason is they have difficulty in accepting the explanation from teacher. To  follow-up that problem, the teacher will give more attention to the activities that can improve concluded skills. The conclusion of this research is that through the PjBL (Project Based Learning) model can improve the concluding skill at the science learning 3rd grade at one of  elementary school in the academic year 2017/2018.